Legislation to foster and support the insect industry: something for Malaysia to ponder - Suzana Muhamad Said; Yeon, Jae Bae (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
Insect as food and feed has become a global topic of interest as an alternative to protein source. Prediction of food scarcity in the future has also bringing the subject on its importance. Many countries have developed the insect industry yet the legal framework concerning it is still at infancy stage and even uncertain. In Malaysia, as of today, the legislation on insect is scattered with no specific legislation. In this regards the existing Malaysia’s legislations only cater for the danger of certain insect such as the Destruction of Disease-Bearing Insects Act 1975 [Act 154]. We explores the need for a structured legislation to foster and support the insect industry in Malaysia. The methodoly used was by exploring the South Korean Act on Fosterage and Support of the Insect Industry as suggestions for Malaysia to consider. Result suggests that Malaysia should have a legislation of its own to regulate the insect industry. The future of insect as food and feed holds a huge potential which Malaysia should not missed out.